The Effect Of Financial Ratio On Company Value With Inflation As A Moderation Variable - Herman Ruslim; Michael Michael (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2019)
This study empirically examines the effect of capital structure, company growth, and profitability on firm value with inflation as a moderating variable in issuers in 2012-2015. The sample of this study was 245 issuers. The research method uses the Generalized Method of Moments (GMM) method. The result of this study is indicated that partially positive and significant effect on firm value (PBV) is the capital structure variable (DAR) and profitability (ROA), while company growth (growth) partially has a negative and no significant effect on firm value. Therefore, inflation moderates the effect of the relationship of profitability on firm value. The result of Simultaneous test showed that there is a significant effect of capital structure, company growth, profitability, and inflation simultaneously on firm value. This is indicated by the result of R-squared 19.3141% which indicated that variations in company value can be explained by variable capital structure, company growth, profitability and inflation of 19.3141% and the remaining 80.6859% explained by other factors.